Measuring the NAIRU: Evidence from Seven Economies - Laubach, Thomas (The Review of Economics and Statistics, 2001)
Several specifications of state-space models are used to obtain estimates of the NAIRU for the G7 except Japan, plus Australia, over the past 28 years. A Phillips curve-type regression is shown to deliver estimates that do not mimic low-frequency movements in unemployment rates, even when a drift is included in the specification of the NAIRU. Standard errors around the estimates are extremely large. Using information about the behavior of unemployment, in addition to inflation, alleviates both these shortcomings.